Circulating Anti-cytolethal Distending Toxin B and Anti-vinculin Antibodies as Biomarkers in Community and Healthcare Populations With Functional Dyspepsia and Irritable Bowel Syndrome. Issue 7 (July 2019) - Talley, Nicholas J.; Holtmann, Gerald; Walker, Marjorie M.; Burns, Grace; Potter, Michael; Shah, Ayesha; Jones, Michael; Koloski, Natasha A.; Keely, Simon
Abstract : OBJECTIVES: Anti-cytolethal distending toxin B (CdtB) and anti-vinculin antibodies have been proposed as biomarkers that discriminate irritable bowel syndrome (IBS) diarrhea from inflammatory bowel disease; however, it is unknown whether they can also discriminate patients with IBS and IBS subtypes and functional dyspepsia (FD) from healthy individuals in the general population. We aimed to determine whether anti-CdtB and anti-vinculin can discriminate IBS and FD from health and from organic gastrointestinal (GI) disease. METHODS: Adults were enrolled from 2 Australian studies: (i) a random, population-based study (n = 331) with subjects diagnosed with IBS (n = 63) or FD (n = 61) by modified Rome III criteria or healthy control subjects (n = 246) who did not meet criteria for IBS and/or FD and (ii) an outpatient-based study with subjects diagnosed with IBS (n = 256) and/or FD (n = 55) or organic GI disease (n = 182) by an independent clinician. Serum levels of anti-CdtB/anti-vinculin antibodies were determined by enzyme-linked immunosorbent assay. RESULTS: There was a significantly higher mean value of anti-CdtB in FD vs healthy controls (mean = 2.46 [SD = 0.72] vs mean = 2.14 [SD = 0.77]; P = 0.005) and IBS/FD overlap vs healthy controls (mean = 2.47 [SD = 0.78] vs mean = 2.14 [SD = 0.77]; P = 0.02). There were no significant differences in anti-CdtB in IBS and FD outpatients or IBS/FD subgroups compared with patients with organic GI disease. In terms of anti-vinculin, there were no significant differences between IBS and FD and healthy controls or between IBS and FD and organic GI disease controls. DISCUSSION: We did not confirm that anti-CdtB/anti-vinculin discriminated IBS diarrhea from organic GI disease in Australian subjects. However, we did find higher anti-CdtB in FD and IBS/FD overlap vs healthy controls. Postinfectious FD may be more common than currently recognized.